2012
DOI: 10.1016/j.atmosenv.2012.06.036
|View full text |Cite
|
Sign up to set email alerts
|

Intra-urban spatial variability and uncertainty assessment of PM2.5 sources based on carbonaceous species

Abstract: To identify the sources of PM2.5 – bound carbonaceous species and examine the spatial variability of source contributions in the Denver metropolitan area, positive matrix factorization (PMF) was applied to one year of every sixth day ambient PM2.5 compositional data, including elemental carbon (EC), organic carbon (OC), and 32 organic molecular markers, from four sites (two residential and two near-traffic). Statistics (median, inner quantiles and 5th – 95th percentiles range) of factor contributions, expresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 47 publications
0
11
0
1
Order By: Relevance
“…Both components showed relatively modest concentration enhancements during the day, with peak concentrations around 12:00–14:00 local time. Past studies suggest that OM and sulfate are predominantly regional during summer in the Colorado Front Range [ Hand et al ., ; Xie et al ., ]. Wind rose analyses showed no enhancements in either the OM or the sulfate concentration as a function of wind direction (not shown), consistent with a regional source for both components.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Both components showed relatively modest concentration enhancements during the day, with peak concentrations around 12:00–14:00 local time. Past studies suggest that OM and sulfate are predominantly regional during summer in the Colorado Front Range [ Hand et al ., ; Xie et al ., ]. Wind rose analyses showed no enhancements in either the OM or the sulfate concentration as a function of wind direction (not shown), consistent with a regional source for both components.…”
Section: Resultsmentioning
confidence: 90%
“…Rapid expansion of oil and gas operations over the past decade has contributed to changing air quality in the region [ Pétron et al ., ; Thompson et al ., ]. On the regional scale, sulfate and secondary organic aerosols (SOA) from biogenic VOC emissions make important contributions to aerosol levels [ Hand et al ., ; Xie et al ., ]. Finally, aerosol concentrations in the region are subject to intermittent influences from the long‐range transport of fire, dust, and marine air [ Hallar et al ., ; Young et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…For our study, the Denver metropolitan area is about 80 km to the southeast of the sampling site, and the air masses more frequently originate from the south and southwest in summer periods, as shown in the backward trajectory analysis results (Supplementary Figs S2 and S3). In addition, summer upslope wind conditions are known to prevail in the summer, and these conditions may transport Front Range-derived EC, shown to have increased source strength in the summer43, to higher elevations. As such, emissions from the urban area in and around Denver may contribute to the multiple peaks of EC concentrations observed at our site in the summer and may, therefore, also play a role in summertime WSOC and OC inputs.…”
Section: Discussionmentioning
confidence: 99%
“…This method has been introduced and applied in previous work4376. Briefly, PMF uses an uncertainty-weighted least-squares fitting approach to resolve factor profiles and contributions from a series of compositional data of ambient particles.…”
Section: Methodsmentioning
confidence: 99%
“…Measurement error might be expected to be greater for those PM 2.5 components such as EC and OC that are more affected by local sources than are total PM 2.5 mass or secondary sulfate and nitrate components. However, in a supplemental study in which sampling was carried out in 2009 at three additional sites in the Denver area in addition to the site described in this study, we found little spatial heterogeneity of the PM 2.5 components time series or for pollution sources estimated by positive matrix factorization (PMF) across the four sites [ 34 , 35 ]. We were also reassured by preliminary analyses of the DASH site showing that our PM 2.5 component concentrations were highly correlated (0.70-0.86) over time with those at an EPA Chemical Speciation Network site located 13 kilometers away (Fig.…”
Section: Discussionmentioning
confidence: 80%